Numerical Study of the Effect of Thermal Insulation and Window-to-wall Ratio on Reducing the Thermal Loads of the Residential Sector in Iraq - Abd Hussein; Ahmed saleh; Hamdi Ahmed (Engineering and Technology Journal, 2024)
The climate change that the world is witnessing has cast a greater shadow on the Middle East. Iraq, one of the region's countries, is experiencing harsh thermal conditions. With the increase in population growth in the country, there was a significant development in the housing sector, which exacerbated the thermal loads that the residential sector requires to overcome harsh weather conditions. This leads to increased energy consumption. To reduce this consumption and energy waste, a simulation study was conducted using the TRNSYS program to analyze the thermal behavior of a building whose walls consist of Gypsum, Juss, brick, and mortar, as well as the roof consisting of Gypsum, Juss, and high-density concrete covered with sand and shtyger under weather conditions of Baghdad city with coordinates 33° N latitude and 44° E longitude, and to study the essential parameters such as building envelope, window-to-wall ratio (WWR), and internal sources that have a direct impact on the residential buildings. These parameters were processed and optimized to minimize the thermal loads annually. The results show that the optimal WWR is 25% in the south orientation. The annual thermal load can be reduced by about   49 % when covering the building envelope with a thermal insulation type (stone wall) with a thickness of 5 cm.